Designing With-in Public Organisations : building bridges between public sector innovators and designers - Schaminée, André, ....- (Amsterdam : BIS Publishers, 2018)
Design practices increasingly appeal to public organizations as a new and promising approach, but how can we make collaboration between designers and public sector innovators successful?Worldwide, design thinking is being used to come up with meaningful solutions for wicked social problems. However, the way in which public organizations operate in practice is not always in sync with the ways of working, techniques and mentality of design thinking. This book offers advice on how to ensure that a carefully executed design-thinking process actually leads to the desired change.With the help of a methodological approach and a number of insightful examples, this book illustrates how the practice of designers and public organizations, both on the work floor and in the boardroom, can be connected. This process is not about erasing the differences between designers and public organizations, but about turning these differences into something productive. This book will help to create the right context for an impactful design-thinking process with and within public organizations.
Keywords: Designtheorie; Productdesign